Wischnewsky spots in cases of fatal hypothermia in cattle - Larissa L. Souza; Carolina C. Guizelini; Bruno A. Almeida; Thaísa X. Silva; Acauane S. Lima; Vitor F. Carvalho; David Driemeier; Ricardo Antônio A. Lemos (Pesquisa Veterinária Brasileira, 2024)
ABSTRACT: Wischnewsky spots (WS) are hemorrhagic, non-erosive, and non-ulcerative lesions that affect the gastric mucosa. They are considered common in the stomachs of humans who have died from hypothermia and are rarely described in other animal species. This study describes the occurrence of WS in cattle that had died of hypothermia in two cities in the state of Mato Grosso do Sul. Two properties were visited, and three cattle were necropsied by the team from the Pathological Anatomy Laboratory of the Federal University of Mato Grosso do Sul (LAP-UFMS). The epidemiological conditions and clinical signs of the cattle examined on both properties were similar. The deaths occurred on days when there was a sudden drop in environmental temperature, with continuous rain for more than 24 hours. During the visits, the most affected live cattle were found in sternal decubitus, with their heads resting on their flanks, or laterally in a comatose state, with nystagmus and a rectal temperature below 32°C. Macroscopically, there were multifocal to coalescent red and black areas on the mucosal surface of the abomasums of the three cattle necropsied, mainly at the apex of the folds, oval or punctate in shape, measuring 0.1 to 1.0cm in diameter. Microscopically, these dark areas corresponded to areas of rarefaction of the mucosal epithelial cells associated with hemorrhage and the frequent deposition of golden-brown pigment (hematin) in the extracellular medium. The diagnosis of hypothermia in cattle was based on epidemiology, clinical-pathological examination, and the exclusion of differential diagnoses. The lesions found in the abomasum of cattle that had died from hypothermia were compatible with WS, highlighting the importance of recognizing them in cases of cattle deaths in which this condition is suspected.